Clinical Characteristics of Wolfram Syndrome in Chinese Population and a Novel Frameshift Mutation in WFS1 - Duan, Lian; Li, Qian; Tong, An-Li; Mao, Jiang-Feng; Yu, Miao; Yuan, Tao; Chai, Xiao-Feng; Gu, Feng (Frontiers in Endocrinology, 2018)
Objective: Wolfram syndrome (WS) is a rare, degenerative and hereditary disorder characterized by early-onset diabetes mellitus and optic atrophy. We aim to characterize clinical features in Chinese patients who had been poorly studied until now. Methods: We performed a retrospective review of patients with WS seen in Peking Union Medical College Hospital from 2002 to 2017. Data including demographic data, clinical presentations, examination results, family history, and genetic analysis were described. Results: Six patients with Wolfram syndrome were identified, meeting the diagnostic criteria of coincidence of diabetes mellitus and optic atrophy before 15 years old or existence of 2 WFS1 mutations. All were male, with the median age of 14.5 years (range, 10-19 y). Blood glucose impairment, Optic atrophy and diabetes insipidus were present in all (100%), hearing impairment in four (66.7%), urological abnormalities in four (66.7%), neurological abnormalities in one (16.7%), and endocrine disorder in one (16.7%). Rare presentation includes cataract, glaucoma, and spina bifida occulta. Diabetes was insulin-dependent and not ketosis-onset, with antibody to glutamic acid decarboxylase and islet cell negative. Genetic analysis revealed mutations in WFS1 in three patients. A novel frameshift mutation (p.Asp151Glufs*93) was identified in exon 4 of WFS1. Conclusions: Our series of WS patients indicated that WS is a degenerative disease with a wide and variable spectrum, characterized by early-onset non-autoimmune diabetes mellitus and bilateral optic atrophy. Genetic analysis is recommended when suspected of WS.